Relationship between sedentary behavior and endothelial dysfunction in a cross-sectional study in China - Yang, Ping-ting; Yang, Sai-qi; He, Yong-mei; Wang, Jian-gang; Qin, Yue-xiang; Wang, Ya-qin; Li, Ying (Frontiers in Cardiovascular Medicine, 2023)
Sedentary behavior is a risk factor for several diseases, and previous studies have mostly reported the effects of acute sedentary behavior on vascular endothelial function. Data on the relationship between sedentary lifestyle habits and vascular function in large sample populations are lacking. Therefore, the aim of this study was to assess the correlation between self-reported sedentary behavior and peripheral vascular function in a check-up population from real-world data. Methods We recruited 13,220 participants from two health management centers of general tertiary hospitals located in northern and southern China between 2017 and 2021. All participants had undergone both questionnaires and brachial artery flow-mediated dilation (FMD) measurements. Results In total, 3,205 participants with FMD ≤ 5.0% were identified to have endothelial dysfunction. In a multivariable regression model including lifestyle habits such as sedentary behavior and cardiovascular risk factors, taking leisure sedentary time <2 h/day as a reference, the risk of vascular endothelial dysfunction gradually increased with time: 2–4 h/day (OR = 1.182, 95% CI: 1.058–1.321, P = 0.003), 4–6 h/day (OR = 1.248, 95% CI: 1.100–1.414, P = 0.001) and >6 h/day (OR = 1.618, 95% CI: 1.403–1.866, P < 0.001). Conclusion Longer leisure sedentary time is associated with a higher prevalence of vascular endothelial dysfunction. These findings suggest that leisure sedentary behavior is a risk factor for the occurrence of vascular endothelial dysfunction in the Chinese check-up population.